Corrigendum / Erratum / Retraction - Al-Iqtishad, Jurnal (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Retraction to:Sukmana, R. (2018). Determinantf of Credit and Financing Risk: Evidence of Dual Banking System in Indonesia. Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah (Journal of Islamic Economics). Vol. 10 (1): 189-206. doi: 10.15408/aiq.v10i1.5903.This article has been retracted by the publisher based on the following reasonThis is based on the author's recognition to the editor that the author has committed acts of violation of publication ethics. The author has published a double publication by submitting the same article to two journals at the same time. The author admits that he forgot to have submitted the same article to another journal. This article also has published in the Journal of Islamic Financial Studies (Publisher: University of Bahrain) Vol. 3 (2), December 2017 (http://journals.uob.edu.bh/jifs/contents/volume-1115/articles/article-5448)This article has followed with the procedures that apply to journal management. The author has received the review results, and has improved the article according to the review result.One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere, and also not considered by another journal. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter, and apologies are offered to readers of the journal that this was not detected during the submission process.